2004
DOI: 10.1016/j.tsf.2003.10.055
|View full text |Cite
|
Sign up to set email alerts
|

The metrology of a miniature FT spectrometer MOEMS device using white light scanning interference microscopy

Abstract: b bstractMicro-optical electro-mechanical systems (MOEMS) technology, making use of existing silicon based fabrication techniques shows great potential for making complete miniaturized hybrid devices. Such technology has been used to make a Fourier transform spectrometer based on a time-scanning Michelson interferometer. An electrostatic comb drive actuator moves the scanning mirror over a distance of 40 mm. The measured resolution of the spectrometer is 6 nm at a wavelength of 633 nm. The dimensions of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…2(a)). Finer analysis of step edges showed that the system was extending the measured position by up to 3 µm, resulting in a false location [7]. Analysis of the XZ intensity images reveals the presence of "ghost" fringes extending out into empty space at the top of the step and inwards underneath the bottom of the step (Figure 3(b)).…”
Section: Moems Measurements Using a Standard Wlsi Configurationmentioning
confidence: 99%
See 1 more Smart Citation
“…2(a)). Finer analysis of step edges showed that the system was extending the measured position by up to 3 µm, resulting in a false location [7]. Analysis of the XZ intensity images reveals the presence of "ghost" fringes extending out into empty space at the top of the step and inwards underneath the bottom of the step (Figure 3(b)).…”
Section: Moems Measurements Using a Standard Wlsi Configurationmentioning
confidence: 99%
“…The use of far field imaging and a thin virtual scanning probe plane leads to submicron lateral resolution, nanometric axial resolution and the ability to analyze large areas at high speed non-destructively [3,4,5,6]. In previous work [7] a miniature FT spectrometer made with MOEMS technology [8] was investigated using WLSI to explore some of the challenges of carrying out fast, accurate 3D dimensional metrology on such devices. The spectrometer is based on a scanning Michelson interferometer, for use in miniature low cost applications.…”
Section: Introductionmentioning
confidence: 99%
“…A powerful microscope configuration for high-resolution optical coherence tomography applications is based on a Linnik interference microscope with high-numerical-aperture objectives 1 . The full-field OCT (FF-OCT) technique is based on whole field imaging and white-light scanning interference microscopy (WLSI), also known as coherence scanning interferometry (CSI) [2][3][4] . This technique is typically used to measure the thickness and internal structures of transparent and diffusing layers by the detection of multiple fringe envelope signals.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated the use of coherence scanning interferometry (CSI) in the characterization of the topography of a miniaturised MOEMS FT spectrometer [4] and of DOEs made using photoablation of an intermediate resist layer [5]. The particularity of CSI is that it allows deep characterisation (< 150 µm) with nm axial sensitivity on smooth surfaces over wide elds (mm) [6].…”
Section: Introductionmentioning
confidence: 99%